lean2/library/data/list/basic.lean
Leonardo de Moura bbff564a1c feat(frontends/lean): persistent notation in sections
Signed-off-by: Leonardo de Moura <leonardo@microsoft.com>
2014-09-06 11:14:20 -07:00

280 lines
9.3 KiB
Text
Raw Blame History

This file contains ambiguous Unicode characters

This file contains Unicode characters that might be confused with other characters. If you think that this is intentional, you can safely ignore this warning. Use the Escape button to reveal them.

----------------------------------------------------------------------------------------------------
--- Copyright (c) 2014 Parikshit Khanna. All rights reserved.
--- Released under Apache 2.0 license as described in the file LICENSE.
--- Authors: Parikshit Khanna, Jeremy Avigad
----------------------------------------------------------------------------------------------------
-- Theory list
-- ===========
--
-- Basic properties of lists.
import tools.tactic
import data.nat
import logic tools.helper_tactics
-- import if -- for find
open nat
open eq_ops
open helper_tactics
inductive list (T : Type) : Type :=
nil {} : list T,
cons : T → list T → list T
namespace list
-- Type
-- ----
infix `::` := cons
section
variable {T : Type}
theorem induction_on [protected] {P : list T → Prop} (l : list T) (Hnil : P nil)
(Hind : forall x : T, forall l : list T, forall H : P l, P (cons x l)) : P l :=
rec Hnil Hind l
theorem cases_on [protected] {P : list T → Prop} (l : list T) (Hnil : P nil)
(Hcons : forall x : T, forall l : list T, P (cons x l)) : P l :=
induction_on l Hnil (take x l IH, Hcons x l)
notation `[` l:(foldr `,` (h t, cons h t) nil) `]` := l
-- Concat
-- ------
definition concat (s t : list T) : list T :=
rec t (fun x : T, fun l : list T, fun u : list T, cons x u) s
infixl `++` : 65 := concat
theorem nil_concat {t : list T} : nil ++ t = t
theorem cons_concat {x : T} {s t : list T} : (x :: s) ++ t = x :: (s ++ t)
theorem concat_nil {t : list T} : t ++ nil = t :=
induction_on t rfl
(take (x : T) (l : list T) (H : concat l nil = l),
show concat (cons x l) nil = cons x l, from H ▸ rfl)
theorem concat_assoc {s t u : list T} : s ++ t ++ u = s ++ (t ++ u) :=
induction_on s rfl
(take x l,
assume H : concat (concat l t) u = concat l (concat t u),
calc
concat (concat (cons x l) t) u = cons x (concat (concat l t) u) : rfl
... = cons x (concat l (concat t u)) : {H}
... = concat (cons x l) (concat t u) : rfl)
-- Length
-- ------
definition length : list T → := rec 0 (fun x l m, succ m)
theorem length_nil : length (@nil T) = 0 := rfl
theorem length_cons {x : T} {t : list T} : length (x :: t) = succ (length t)
theorem length_concat {s t : list T} : length (s ++ t) = length s + length t :=
induction_on s
(calc
length (concat nil t) = length t : rfl
... = zero + length t : {add_zero_left⁻¹}
... = length (@nil T) + length t : rfl)
(take x s,
assume H : length (concat s t) = length s + length t,
calc
length (concat (cons x s) t ) = succ (length (concat s t)) : rfl
... = succ (length s + length t) : {H}
... = succ (length s) + length t : {add_succ_left⁻¹}
... = length (cons x s) + length t : rfl)
-- add_rewrite length_nil length_cons
-- Append
-- ------
definition append (x : T) : list T → list T := rec [x] (fun y l l', y :: l')
theorem append_nil {x : T} : append x nil = [x]
theorem append_cons {x y : T} {l : list T} : append x (y :: l) = y :: (append x l)
theorem append_eq_concat {x : T} {l : list T} : append x l = l ++ [x]
-- add_rewrite append_nil append_cons
-- Reverse
-- -------
definition reverse : list T → list T := rec nil (fun x l r, r ++ [x])
theorem reverse_nil : reverse (@nil T) = nil
theorem reverse_cons {x : T} {l : list T} : reverse (x :: l) = append x (reverse l)
theorem reverse_singleton {x : T} : reverse [x] = [x]
theorem reverse_concat {s t : list T} : reverse (s ++ t) = (reverse t) ++ (reverse s) :=
induction_on s (concat_nil⁻¹)
(take x s,
assume IH : reverse (s ++ t) = concat (reverse t) (reverse s),
calc
reverse ((x :: s) ++ t) = reverse (s ++ t) ++ [x] : rfl
... = reverse t ++ reverse s ++ [x] : {IH}
... = reverse t ++ (reverse s ++ [x]) : concat_assoc
... = reverse t ++ (reverse (x :: s)) : rfl)
theorem reverse_reverse {l : list T} : reverse (reverse l) = l :=
induction_on l rfl
(take x l',
assume H: reverse (reverse l') = l',
show reverse (reverse (x :: l')) = x :: l', from
calc
reverse (reverse (x :: l')) = reverse (reverse l' ++ [x]) : rfl
... = reverse [x] ++ reverse (reverse l') : reverse_concat
... = [x] ++ l' : {H}
... = x :: l' : rfl)
theorem append_eq_reverse_cons {x : T} {l : list T} : append x l = reverse (x :: reverse l) :=
induction_on l rfl
(take y l',
assume H : append x l' = reverse (x :: reverse l'),
calc
append x (y :: l') = (y :: l') ++ [ x ] : append_eq_concat
... = concat (reverse (reverse (y :: l'))) [ x ] : {reverse_reverse⁻¹}
... = reverse (x :: (reverse (y :: l'))) : rfl)
-- Head and tail
-- -------------
definition head (x : T) : list T → T := rec x (fun x l h, x)
theorem head_nil {x : T} : head x (@nil T) = x
theorem head_cons {x x' : T} {t : list T} : head x' (x :: t) = x
theorem head_concat {s t : list T} {x : T} : s ≠ nil → (head x (s ++ t) = head x s) :=
cases_on s
(take H : nil ≠ nil, absurd rfl H)
(take x s, take H : cons x s ≠ nil,
calc
head x (concat (cons x s) t) = head x (cons x (concat s t)) : {cons_concat}
... = x : {head_cons}
... = head x (cons x s) : {head_cons⁻¹})
definition tail : list T → list T := rec nil (fun x l b, l)
theorem tail_nil : tail (@nil T) = nil
theorem tail_cons {x : T} {l : list T} : tail (cons x l) = l
theorem cons_head_tail {x : T} {l : list T} : l ≠ nil → (head x l) :: (tail l) = l :=
cases_on l
(assume H : nil ≠ nil, absurd rfl H)
(take x l, assume H : cons x l ≠ nil, rfl)
-- List membership
-- ---------------
definition mem (x : T) : list T → Prop := rec false (fun y l H, x = y H)
infix `∈` := mem
-- TODO: constructively, equality is stronger. Use that?
theorem mem_nil {x : T} : x ∈ nil ↔ false := iff.rfl
theorem mem_cons {x y : T} {l : list T} : mem x (cons y l) ↔ (x = y mem x l) := iff.rfl
theorem mem_concat_imp_or {x : T} {s t : list T} : x ∈ s ++ t → x ∈ s x ∈ t :=
induction_on s or.inr
(take y s,
assume IH : x ∈ s ++ t → x ∈ s x ∈ t,
assume H1 : x ∈ (y :: s) ++ t,
have H2 : x = y x ∈ s ++ t, from H1,
have H3 : x = y x ∈ s x ∈ t, from or.imp_or_right H2 IH,
iff.elim_right or.assoc H3)
theorem mem_or_imp_concat {x : T} {s t : list T} : x ∈ s x ∈ t → x ∈ s ++ t :=
induction_on s
(take H, or.elim H false_elim (assume H, H))
(take y s,
assume IH : x ∈ s x ∈ t → x ∈ s ++ t,
assume H : x ∈ y :: s x ∈ t,
or.elim H
(assume H1,
or.elim H1
(take H2 : x = y, or.inl H2)
(take H2 : x ∈ s, or.inr (IH (or.inl H2))))
(assume H1 : x ∈ t, or.inr (IH (or.inr H1))))
theorem mem_concat {x : T} {s t : list T} : x ∈ s ++ t ↔ x ∈ s x ∈ t
:= iff.intro mem_concat_imp_or mem_or_imp_concat
theorem mem_split {x : T} {l : list T} : x ∈ l → ∃s t : list T, l = s ++ (x :: t) :=
induction_on l
(take H : x ∈ nil, false_elim (iff.elim_left mem_nil H))
(take y l,
assume IH : x ∈ l → ∃s t : list T, l = s ++ (x :: t),
assume H : x ∈ y :: l,
or.elim H
(assume H1 : x = y,
exists_intro nil
(exists_intro l (H1 ▸ rfl)))
(assume H1 : x ∈ l,
obtain s (H2 : ∃t : list T, l = s ++ (x :: t)), from IH H1,
obtain t (H3 : l = s ++ (x :: t)), from H2,
have H4 : y :: l = (y :: s) ++ (x :: t),
from H3 ▸ rfl,
exists_intro _ (exists_intro _ H4)))
-- Find
-- ----
-- to do this: need decidability of = for nat
-- definition find (x : T) : list T → nat
-- := rec 0 (fun y l b, if x = y then 0 else succ b)
-- theorem find_nil (f : T) : find f nil = 0
-- :=refl _
-- theorem find_cons (x y : T) (l : list T) : find x (cons y l) =
-- if x = y then 0 else succ (find x l)
-- := refl _
-- theorem not_mem_find (l : list T) (x : T) : ¬ mem x l → find x l = length l
-- :=
-- @induction_on T (λl, ¬ mem x l → find x l = length l) l
-- -- induction_on l
-- (assume P1 : ¬ mem x nil,
-- show find x nil = length nil, from
-- calc
-- find x nil = 0 : find_nil _
-- ... = length nil : by simp)
-- (take y l,
-- assume IH : ¬ (mem x l) → find x l = length l,
-- assume P1 : ¬ (mem x (cons y l)),
-- have P2 : ¬ (mem x l (y = x)), from subst P1 (mem_cons _ _ _),
-- have P3 : ¬ (mem x l) ∧ (y ≠ x),from subst P2 (not_or _ _),
-- have P4 : x ≠ y, from ne_symm (and.elim_right P3),
-- calc
-- find x (cons y l) = succ (find x l) :
-- trans (find_cons _ _ _) (not_imp_if_eq P4 _ _)
-- ... = succ (length l) : {IH (and.elim_left P3)}
-- ... = length (cons y l) : symm (length_cons _ _))
-- nth element
-- -----------
definition nth (x : T) (l : list T) (n : ) : T :=
nat.rec (λl, head x l) (λm f l, f (tail l)) n l
theorem nth_zero {x : T} {l : list T} : nth x l 0 = head x l
theorem nth_succ {x : T} {l : list T} {n : } : nth x l (succ n) = nth x (tail l) n
end
end list